EXPLORING WOMEN'S LANGUAGE STYLES IN INSTAGRAM CAPTIONS DURING THE PALESTINE-ISRAEL CONFLICT - Zahirah, Daffa Nafisah; Navtafilofa, Sesha Amara; Afandi, Roy Ramadhani; Degaf, Agwin (JURNAL LITERASI, 2024)
Abstract: This research aims to examine the different language styles used in social media captions, particularly those related to the conflict between Palestine and Israel. Using a qualitative approach and descriptive analysis techniques, the study analyzes fifteen posts from various female Instagram accounts. Data collection involved accessing Instagram via smartphones, searching for relevant posts and hashtags, and capturing screenshots of posts with captions pertaining to the conflict. Martin Joos' (1976) theory on language styles was employed to categorize the data. The findings reveal four types of language styles: frozen style (23.8%), casual style (34.9%), formal style (12.7%), and intimate style (28.6%). The casual style emerged as the most prevalent, while the consultative style was absent, likely due to its common use in oral or direct conversations rather than written captions. This study highlights the predominance of casual language in social media discourse related to sensitive geopolitical issues. Keywords: Language styles, social media captions, Palestine-Israel conflict, Martin Joos.